Building Professionals' Capacity: The Cascading Coaching Model. (October 2022) - Chung, Moon Y.; Lee, James D.; Meadan, Hedda; Sands, Michelle M.; Haidar, Ban Sleiman
The importance of family engagement in their children's education and treatment is emphasized by researchers, professional organizations, and legislatures. Providing services with caregivers via telepractice has gained more support and is becoming especially timely due to the current pandemic and social distancing requirements. Professionals, such as board-certified behavior analysts (BCBAs), who work with caregivers with children with disabilities may benefit from receiving professional development on strategies for building better rapport with caregivers and coaching them to bring about maximum clinical efficacy. The current pilot study replicated an earlier study by Meadan et al. to examine the effects of the Coaching Caregiver Professional Development (CoCarePD) intervention package, in which BCBAs received training and coaching from researchers via telepractice, on their caregiver coaching practices. A single-case, multiple-probe design study across three BCBAs was conducted, and findings support a functional relationship between the CoCarePD and BCBAs' use of coaching practices.